2021
DOI: 10.1002/qj.3954
|View full text |Cite
|
Sign up to set email alerts
|

Large‐eddy simulation of foehn–cold pool interactions in the Inn Valley during PIANO IOP 2

Abstract: Processes of cold‐air pool (CAP) erosion in an Alpine valley during south foehn are investigated based on a real‐case large‐eddy simulation (LES). The event occurred during the second Intensive Observation Period (IOP 2) of the PIANO field experiment in the Inn Valley, Austria, near the city of Innsbruck. The goal is to clarify the role of advective versus turbulent heating, the latter often being misrepresented in mesoscale models. It was found that the LES of the first day of IOP 2 outperforms a mesoscale si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(95 citation statements)
references
References 66 publications
4
91
0
Order By: Relevance
“…Based on observations during a föhn case, Haid et al (2020) found the same order of magnitude for heating in the CAP by turbulent mixing and by the sum of all processes (net effect). A similar result was found by Umek et al (2020) based on large-eddy simulations for the same event. However, they also noted that turbulent CAP erosion exhibits large spatial heterogeneity due to the complex three-dimensional flow structure in valleys.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Based on observations during a föhn case, Haid et al (2020) found the same order of magnitude for heating in the CAP by turbulent mixing and by the sum of all processes (net effect). A similar result was found by Umek et al (2020) based on large-eddy simulations for the same event. However, they also noted that turbulent CAP erosion exhibits large spatial heterogeneity due to the complex three-dimensional flow structure in valleys.…”
Section: Introductionsupporting
confidence: 88%
“…Similar results were found by Lareau and Horel (2015b) based on idealized simulations. Furthermore, turbulent erosion induced by shear-flow instability was identified as an important process in large-eddy simulations (Fritts et al 2010;Umek et al 2020). This is in accordance with the results of Sheridan (2019) who stated for two-dimensional idealized simulations that shear-induced vertical mixing can play a crucial role in CAP erosion.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations